Improving The Quality of Life of Urban Communities - Maria Gabriela Mbinu; Abbie Colley (International Research and Development for Human Beings (IRDH), 2024)
This research aims to evaluate the Malang City government's urban farming program and its impact on improving the quality of life for urban residents in terms of food security. The study adopts qualitative research methods and descriptive analysis. The findings indicate that the urban farming program, planned collaboratively by the PKK and Malang City Food and Agriculture Security Service, has been successfully implemented in Dinoyo Village and Penanggungan Village. These initiatives have had a significant positive impact on the communities, enabling them to meet their food needs independently using the available land. However, the implementation of urban farming in Malang City faces certain obstacles, including the absence of clear policy guidelines, limited community understanding, and inadequate supervision and evaluation process after program implementation and support.